الحب والحرمان في شعر مزاحم العقيلي - يونس, علي (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
مزاحم العقيلي شاعر إسلامي ظل بعيداً عن الأضواء وراقداً في دائرة النسيان, لأنه لم يحظ إلا بالقليل من اهتمام الدارسين للأدب العربي القديم, على الرغم من أهميته ومكانته الشعرية التي لا تقل مكانة عن أقرانه من الشعراء المشهورين في عصره. وحتى لا يبقى الشاعر في دائرة العتمة والإهمال, فقد جاءت الدراسة محاولة جادة للتعريف به من جهة, وللوقوف على أشعاره من جهة أخرى, ولكن نظراً لغنى مادته الشعرية التي تتجاوز حدود هذه الدراسة ومساحتها, فقد اكتفيت بالوقوف على أشعار الحب في شعره, وهي أشعار حافلة بالعديد من قصص الحب والحرمان, فإذا الاحباطات والإخفاقات تلاحقه من محبوبة إلى أخرى من غير أن يلقى منهن مكافأة على حبه وإخلاصه, بل نراه يحصد المزيد من الألم والحسرة والعذاب. وقد كشفت القراءة التحليلية لأشعار الحب هذه, عن غناها بالرموز والمضامين التي جمعت تشكيلاً جمالياً متنوعاً من الصور المتناقضة, علماً أن دراسة واحدة لا تكفي لإعطاء مزاحم حقه كاملاً, فما أبدعه من أشعار يفتح الباب واسعاً لمقالات وأبحاث غنية أخرى. The Islamic poet "Muzahim Al-Oqeily" remained without illuminations and rests in forget. So, he received a little attention only from scholars of the ancient Arabic literature, in spite of his importance and the position of his poetry, which is not less than the positions of his all famous poet peers of that time. Since this poet should not stay in the circle of darkness and negligence, this study makes a serious attempt to illustrate him, on the one hand, and to explore his poems on the other. However, due to the richness of his poetry materials, which are beyond this study limits and space, only his poetry of love was discussed. This poetry is full of different love and denial stories. So, he was followed by frustrations and failures from one darling to another without getting a reward for his love and dedication. In contrast, we see him reaping more pain, anguish and suffering. Analytical reading of this poems of love, revealed their richness in symbols and contents, which collected several aesthetic forms of divers contrasting images. It is worth to note that one study is not enough to give Muzahim's what he deserves, because his poetry creations offer many chances for other rich articles and researches.